An introduction to inferential statistical tests. (SAGE Publications Ltd, 2017)
Professors Eric Jensen and Charles Laurie provide an outline of inferential statistical testing. Their explanation describes categorical, ordinal, and interval variables, as well as how to run tests on data collected to determine if a null hypothesis can be rejected.